Magnetostratigraphic and uranium-series dating of fossiliferous cave sediments in Jinyuan Cave, Liaoning Province, northeast China. (30th July 2021) - Ge, Junyi; Deng, Chenglong; Shao, Qingfeng; Wang, Yuan; Tang, Ruiping; Zhao, Bo; Cheng, Xiaodong; Jin, Changzhu; Olsen, John W.
Abstract: Chronological sequences of Quaternary terrestrial mammalian faunas can provide important information about the evolutionary history of mammals, regional biostratigraphy and paleoenvironmental changes. Here we report the results of studies of a thick, nearly-continuous sedimentary sequence from Jinyuan Cave, in Liaoning Province, northeast China; the sequences contains four mammalian faunas ranging in age from the Late Pliocene to the late Middle Pleistocene. Detailed paleomagnetic and U-series age determinations date the upper unit of the sedimentary sequence to 2.2–0.3 Ma. The results suggest that cave development and infilling were closely associated with the tectonic evolution of the Bohai Basin, including the subsidence of the basin and the uplift of the surrounding mountains, such as Luotuo Hill. Together with the large mammalian faunas from both south and north China, we suggest that these mammalian faunas were smaller in size and lower in species diversity during the Middle Pleistocene Transition (MPT) (1.2–0.7 Ma) than in the earlier and later Pleistocene. This indicates that major climatic variations during the MPT in north China may have reduced their taxonomic abundance and diversity. The extremely warm and wet interglacial climates that followed the MPT in monsoonal East Asia provided an ecological niche for the evolution and migration of these mammalian faunas, resulting in an increase in the numbers and diversity of mammals in East Asia.